A CASE OF HEART FAILURE UNVEILING HIDDEN ACROMEGALY - Zohdi, Wan Awatif Wan Mohd; Esham, D N Ezrinah D N; Azizi, Ku Noor Aimi Ku (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Acromegaly is a rare disease caused by hypersecretion of growth hormone. Cardiovascular disease is the most common comorbidity in acromegaly and constitutes a leading cause of mortality. However, there is currently limited direct literature addressing heart failure with preserved ejection fraction (HFpEF) in acromegaly. We present a case of acromegaly presenting with heart failure. CASE At a district hospital in Kedah, a 46-year-old female with a known case of hypertension since the age of 23 years old presented with dyspnoea on exertion, orthopnoea, and bilateral leg swelling. She had significant weight gain following her hypertension diagnosis. Her physical examination showed a weight of 121 kg, height of 1.75 m, and body mass index of 46.7 kg/m². Her blood pressure was 141/89 mm Hg with a heart rate of 90 beats/min. Lung examinations revealed coarse crepitations with bilateral pitting oedema. A comprehensive physical examination revealed spade-like hands and feet, prominent supraorbital ridges, widening of teeth spaces with thick lips, and an enlarged nose. Given the characteristic clinical findings, we suspected the provisional diagnosis of acromegaly. Chest radiography showed cardiomegaly with congestive features. Echocardiogram revealed an ejection fraction of 57%, mildly dilated left atrium with grade 1 diastolic dysfunction which is consistent with HFpEF. Laboratory workup showed elevated insulin-like growth factor 1 level of 278.4 ng/mL (normal 56.8–194.5 ng/mL). Subsequently, she was referred to an endocrinologist in a tertiary centre for further investigation and treatment. CONCLUSION This case highlights the critical importance in recognizing acromegaly as a rare underlying cause of cardiac manifestations. The clinical suspicion based on physical examination can facilitate prompt diagnosis to prevent early cardiovascular death in acromegaly patients. Clinicians should maintain a high index of suspicion for endocrine disorders that may present with cardiovascular manifestations.